Efektivitas Pendekatan Quantum Learning Terhadap Peningkatan Hasil Belajar IPS Siswa Kelas IV SD Negeri 223 Sumpang Minangae Kabupaten Bone - Hajja Rosmini (JIKAP PGSD: Jurnal Ilmiah Ilmu Kependidikan, 2022)
The problem in this study is whether the application of the Quantum Learning approach can improve the learning outcomes of fourth grade students at SD Negeri 223 Sumpang Minangae. While the purpose of this study was to determine the process of applying the Quantum Learning approach to improve social studies learning outcomes for fourth grade students of SD Negeri 223 Sumpang Minangae. This research is a descriptive study with the focus of the research being the fourth grade students of SD Negeri 223 Sumpang Minangae. The data collection was done by using test, observation, and interview techniques, while the data analysis technique used was the analysis of the data in this study before collecting the research data. Data analysis was carried out by comparing the results, interviews with indicators at the reflection stage of the research cycle. The data collected is set in a qualitative research. The results of the study can be said that through the application of the quantum learning method to improve student learning outcomes in social studies learning for fourth grade students of SD Negeri 223 Sumpang Minangae, the results of the study show that the value of social studies learning has increased from the implementation of the first cycle to the second cycle.